Evaluation of the Effectiveness of Artificial Intelligence System in Higher Education Curriculum Management - Anri Naldi; Nurkadri Nurkadri; Mansyur Srisudarso; Didik Cahyono; Suyitno Suyitno (International Journal of Educational Narratives, 2024)
Background. The learning of natural sciences at Islamic elementary schools in Central Ternate has not yet been integrated with the verses of the Koran. There is still a dichotomy between general knowledge and religious knowledge, even though all of this knowledge originates from the Al-Quran. Purpose. This study aims to dig deeper into the integration of verses from the Koran in science learning at Islamic Elementary Schools in Central Ternate City. This study uses a phenomenological approach to the triangulation model. Respondents in this study were 15 people consisting of 3 school principals, 3 class teachers, and 9 grade 4 students of SD Islamiyah in Central Ternate City. Method. Data collection techniques in this study are observation, documentation, and in-depth interviews related to research variables. The research data were analyzed descriptively.   Results. The results showed that based on the results of observations of learning activities in class 4 SD Islamiyah in Ternate City, it had not been found integrating science learning with verses from the Qur'an, meaning that learning only focused on science subject matter, had nothing to do with verses. Al-Qur'an related to science material being taught, but students' character building can be seen clearly when learning activities take place. Conclusion. The same thing was also obtained from the results of interviews with school principals, class teachers, and students that the implementation of learning by integrating verses of the Qur'an had not been carried out because the school was still carrying out learning by referring to the established curriculum, so there was no connection between Al -Qur'an and any subject matter conveyed by the class teacher.